PENGEMBANGAN PANDUAN PELATIHAN CREATIVE PROBLEM SOLVING UNTUK MENCEGAH BULLYING DI SMP - Sukarno, Triwibowo Probo; Handarini, Dany Moenindyah (Jurnal Kajian Bimbingan dan Konseling, 2016)
This research aims to developing the creative problem solving manual for preventing bullying among junior high school students which acceptable on accuracy, utility, and implementatively. This research method is adapted from procedural research and development Borg & Gall model (1983). Expert and prospective user analyzed by inter-rater agreement (Grinnell, 1988). Agreement result of 3 guidance and counseling experts from accuracy aspect is high, utility is high, and implementatiely is very high. Agreement of 3 prospective users from accuracy is high, utility is high, and implementatively is very high. The conclusion of the test is, this training guide product acceptable.